Training and assistance in making village profiles as a branding facility for Pujon Kidul tourism village - Suhermanto, Dedik Fitra; Sugiharto, Mochamad Aan; Mas’udi, Syasya Yuania Fadila (Community Empowerment, 2021)
The purpose of this service is to provide knowledge to village officials and the community of Pujon Kidul Village about the importance of the Village Profile. The Village Profile is very much needed as a means of socializing and actualizing the potential that exists in the village. However, Pujon Kidul Village, which is known as the Tourism Village, does not yet have an official village profile. So that the socialization of village potential is not optimal. The special target to be achieved in this service is the compilation of the Pujon Kidul Village profile which is officially managed by the community and / or village officials with online media in the form of websites and offline media. For this reason, training in making a good and attractive village profile is needed so that the aims and objectives of creating a village profile for socialization and promotion of village potentials will be carried out well. This service was carried out using the Focus Group Discussion (FGD) method which involved village officials and BUMDes managers which resulted in three agreements. First, a more adequate and informative website was developed. Second, a village profile video was made and a booklet was compiled. Third, the use of the media is to maximize village promotion through online and offline.